ADMINISTRATIVE DECISIONS IN THE PHARMACEUTICAL SECTOR: A COMPARATIVE ANALYSIS OF INDONESIA AND THE UNITED STATES - Tjandrawinata, Raymond R.; Heliany, Ina (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2025)
Administrative decisions in the pharmaceutical industry influence the balance between innovation protection and drug accessibility, particularly in developing countries like Indonesia. This study evaluates the impact of administrative decisions on Indonesia's pharmaceutical sector by comparing them with the policies of the United States Food and Drug Administration (FDA). The research employs a descriptive-qualitative approach, analyzing administrative law theory, Gustav Radbruch’s balance of law theory, intellectual property, and legal realism. The findings reveal that administrative decisions often reinforce patent protection, which promotes innovation but limits drug access, especially for low-income populations. In Indonesia, the National Agency of Drug and Food Control (BPOM) faces challenges in meeting public needs amidst limited adaptive regulations. Barriers to implementing compulsory licensing and international pressures complicate drug distribution arrangements, particularly in emergency situations. This study recommends harmonizing regulations with international standards, enhancing transparency in decision-making, and implementing compulsory licensing to address the tension between patent protection and accessibility. This approach is expected to create a more inclusive, equitable, and responsive pharmaceutical regulatory framework that meets societal needs without compromising innovation